“Illumination of the Topic of Youth in the State Drama Theater of Uzbekistan” (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
In this article, enlightened moderns, who understood that it is impossible to form the spirituality of the people, enrich the Islamic spirituality with new knowledge, and in the historical process, they made their proper contribution to the formation of the spirituality of people's faith and worldview. if there is, it is said that they sacrificed their lives.